Turning the Tide on Poverty: Strategies and challenges related to tackling poverty in rural communities in the South. Issue 3 (26th May 2016) - Worthy, Sheri Lokken; Beaulieu, Lionel J.
Abstract: This special issue of Community Development on the Turning the Tide on Poverty (Tide) initiative addresses a number of elements that are vital to the ability of impoverished rural areas to take steps to improve conditions in their communities. This article is intended to highlight the key findings from this study in the southern US that are of value to community development practitioners. The Tide research team devoted special attention to the efforts that have become part of the fabric of many communities engaged in the Tide program. Our observations include evidence of the expanded involvement of local residents in the civic life of their communities, the renewal of economic activities in the target communities, and the accumulation of valuable lessons learned. These lessons can help inform and guide the poverty alleviation and improvement efforts of other communities that have decided to promote a brighter future for their places of residence. Furthermore, we discuss policy implications of our "in-the-field" work in low-wealth communities.